1974
DOI: 10.1159/000231138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soluble Antigen on IgE Responses in the Mouse

Abstract: Three injections of 100 μgof soluble ovalbumin (Ova) significantly reduced IgE responses of DBA/1J mice to immunization with 0.1 μgOva in Al(OH)3 gel, whereas IgG1 responses were not similarly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 7 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…In these animals, oral exposures to antigen may result in serum [50][51][52] and mucosal secondary responses [52]. A few reports have suggested that more prolonged oral exposures may result in suppression [53], including the formation of IgE [54,55] and DTH reactions [56]. Intense and prolonged feeding with the antigen may abort antibody formation only during the first 2 weeks after primary immunization [51].…”
Section: Oral Tolerance After Primingmentioning
confidence: 99%
“…In these animals, oral exposures to antigen may result in serum [50][51][52] and mucosal secondary responses [52]. A few reports have suggested that more prolonged oral exposures may result in suppression [53], including the formation of IgE [54,55] and DTH reactions [56]. Intense and prolonged feeding with the antigen may abort antibody formation only during the first 2 weeks after primary immunization [51].…”
Section: Oral Tolerance After Primingmentioning
confidence: 99%
“…7 indicate that the secondary antihapten IgG antibody response was enhanced by homologous hapten-carrier (DNP-EA) and carrier (EA) alone. In addition, the IgG response was not enhanced by hapten Antigen-induced regulation of the reaginic antibody response in mice has been shown or postulated to occur in two ways: (a) directly at the B-cell level (2,7,26), and (b) indirectly, through helper or suppressor T cells (3)(4)(5)10). By analyzing the anti-DNP IgE response by the primed lymphocytes to secondary stimulation by hapten coupled to homologous carrier (DNP-EA), hapten coupled to heterologous carrier (DNP-BGG), and carrier (EA) alone, we demonstrated that the antigen-induced inhibition of IgE production was caused by hapten and not by carrier.…”
Section: Secondary Antihapten Igm and Igg Responses Inmentioning
confidence: 99%
“…The regulation of the IgE immune response has been shown to be dependent upon the dose of the antigen employed for the induction of the primary response (1) as well as during secondary antigenic stimulation (2)(3)(4)(5), persistent IgE responses being favored by low doses of antigen. Takatsu and Ishizaka, utilizing passive transfer experiments in mice, demonstrated that high doses of antigen prevented the development of antigen-specific IgE bone marrow-derived lymphocytes (B cells) 1 in the spleens of the treated mice (3), caused a decreased carrier-specific helper activity of the thymus-derived lymphocyte (T cells) in the spleens (4), and that these effects were due to the induction of T suppressor cells by the high doses of antigen (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Re cently many experiments have been carried out to elucidate immunoregulatory mecha nisms of IgE antibody formation, which may eventually bring crucial information on induction of specific tolerance to allergens [5][6][7][8][9][10], Meanwhile, several approaches have been introduced to manipulate im mune systems in such a way that only limit ed amounts of IgE antibodies are produced in response to various haptens [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Of particular interest was the treatment of IgE low responder mice with complete Freund's adjuvant which induced antigen-nonspecific suppressor T cells [24].…”
Section: Introductionmentioning
confidence: 99%